Solar Power Generation by Using Vk0001 Panel (International Journal of Communication Systems and Network Technologies, 2021)
Solar power is the conversion of sunlight into electricity, either directly using photovoltaic (PV), or indirectly using concentrated solar power (CSP). Concentrated solar power systems use lenses or mirrors and tracking systems to focus a large area of sunlight into a small beam. This storage energy we are using for home applications, this voltage retrieves and converts DC to AC voltage to activate CFL bulb. Received voltage from the SOLAR VOLTAIC is charges the battery and it converts the voltage in to 230 voltage by the way it amplifies the current to activate CFL bulb. Before years natural power generation is expandable and costly project for home and industrial areas but these days it might be very common topic for installing natural power sources like solar panels and wind. My idea about power generation is that we can’t create natural power sources but we can retrieve power which already exists like sun and air. Power generation from sun with solar panel only existed. What happen if an invention generates power from sun without solar panel? This project publish reveals the power generation form without solar panel I named this panel name as “VK0001 panel”.
Keywords: Concentrated Solar Power; Photovoltaic; Solar Panel; VK0001 Panel